2021
DOI: 10.1021/acs.biochem.0c00950
|View full text |Cite
|
Sign up to set email alerts
|

HutW from Vibrio cholerae Is an Anaerobic Heme-Degrading Enzyme with Unique Functional Properties

Abstract: Increasing antibiotic resistance, and a growing recognition of the importance of the human microbiome, demand that new therapeutic targets be identified. Characterization of metabolic pathways that are unique to enteric pathogens represents a promising approach. Iron is often the rate-limiting factor for growth, and Vibrio cholerae, the causative agent of cholera, has been shown to contain numerous genes that function in the acquisition of iron from the environment. Included in this arsenal of genes are operon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…To test this possibility, we performed quantification analysis and compared the reaction efficiencies on the two substrates, hemin and PPIX. Because accurate quantification of anaerobilin is impractical owing to its instability, [ 33 ] dAdoH and SAH were used as indicators of the reaction efficiency. A detailed time course analysis of ChuW reaction showed that hemin is a much better substrate than the metal‐free PPIX, as the yields of both dAdoH and SAH in the reaction with hemin are generally more than 2‐folds compared to those in the reaction with PPIX (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…To test this possibility, we performed quantification analysis and compared the reaction efficiencies on the two substrates, hemin and PPIX. Because accurate quantification of anaerobilin is impractical owing to its instability, [ 33 ] dAdoH and SAH were used as indicators of the reaction efficiency. A detailed time course analysis of ChuW reaction showed that hemin is a much better substrate than the metal‐free PPIX, as the yields of both dAdoH and SAH in the reaction with hemin are generally more than 2‐folds compared to those in the reaction with PPIX (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the latter, the methylene radical is added to a double bond, resulting in a methyl transfer reaction and, in many cases, further radical-catalyzed chemical rearrangements . For both ChuW and HutW, this includes the β-scission of a carbon–carbon bond, resulting in opening of the porphyrin ring along with the liberation of the iron atom. , …”
Section: Mechanism Of Chuw and Hutwmentioning
confidence: 98%
“…Similarly, V. cholera also expresses an enzyme, HutW (39% sequence identity with ChuW), that is capable of opening the porphyrin ring under anaerobic conditions . However, in contrast, V.…”
Section: Rsmts In Heme Biosynthesis and Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Fe must be liberated from the tetrapyrrole ring of haem via the activity of haem oxygenases in the bacterial cytosol 30 . Haem oxygenases are classified into five different enzyme families including the HO-1 family, the IsdG family, ChuZ, ChuW and HutW 31 , 32 .…”
Section: Fe In Infection and Immunitymentioning
confidence: 99%